Preventive Health Strategies for Farm Housewives in Southern Tokushima Prefecture - INOUE, Hiroshi; MINAMI, Yoshiko; KATO, Kazuichi (JOURNAL OF THE JAPANESE ASSOCIATION OF RURAL MEDICINE, 1985)
The subjects are farm housewives in two different agricultural communities of southern Tokushima Prefecture. Most of them are engaged in mixed farming on hilsides facing south. The climate is mild all the year around. The people in the two communities, like others in the district, undergo medical checkups regularly executed under the outreach health program of our hospital. In order to obtain data related to their way of living and working conditions, a questionnaire was conducted. In a similar way, a survey was carried out to measure the change in the attitude of the subjects toward health care after medical examination and consultation. In Community A, the economy is largely based on orange growing in vinyl-covered hothouses and bamboo shoots. Of the housewives who responded to our survey, 87.3% said their livelihood depends chiefly on agriculture. Working hours were longest among those in their 40s, 26.8% of whom were found suffering from anemia, in the latest health checkup. Lower levels of neutral fat and a lower degree of albuminurea were noted among those aged 40 or under. These findings suggest that health promotion measures be taken from the standpoint of nutrition. The latest health checkup also revealed that the health conditions remained poor among those who had given little thought to the results found in the previous group medical examination. In Community B, agriculture is dominated by paddy rice and orange growing. But the community is suburban. In formulating a health control program for women in Community B, emphasis should be placed on prevention of hypertension, obesity and other conditions associated with the adult disease.